Arti Penting Irian Barat Bagi Indonesia - Dina Ulayani Harahap; Marzius Insani; Henry Susanto (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2022)
Abstract: The Importance of West Irian for Indonesia. Historically, Indonesia was a former colony of the Dutch East Indies or the former Dutch East Indies. The issue of West Irian as a continuation of the dispute between Indonesia and the Netherlands officially only arose at the enda of 1949. At the time, Indonesia was making vigorous efforts to find a away out through negotiations to resolve political disputes between the two sides, by the intercession of the United Nations (UN). The research method used in this study is, History research method, as for the stages of Historical research, namely, heuristics, criticsm, interpretation, and historiography. The data analysis techniques used are historical data analysis techniques. Using documentation and library data collection techniques. A dispute with the Dutch Colonial Government as a result of the colonialist’s appetite to occupy Indonesian territory was resolved in the hague through the round table conference in 1949 which resulted in Dutch recognition of Indonesia’s sovereignty and independence. However, in the conference there is still an unresolved issue, namely the status of West Irian. The purposw of The Liberation Of West Irian from dutch neo-capitalists was Sukarno did not want to be indifference again if West Irian was freed and became the henchman of the liberal capitalist imperialist state that Sukarno considered could harm the existence of the Republic Of Infonesia social democratic state at that time.Keywords: West Irian, Strategy, Profit, Loss.